Application of shareholders’ agreement in the Republic of Latvia and the United Kingdom - Amosejevs, Marks (Riga Graduate School of Law, 2020)
Nowadays, the companies are the most important actors in domestic and international commerce. The company is the legal entity represented by an association of natural or legal persons called members or shareholders. As a general rule, the liability of its shareholders is usually limited by the statutory documents of the company, such as the articles of association. The articles of association serve as the constitution of the company, regulating its structure, organization, existence and relations between its shareholders, relation between the company and its shareholders. However, very often the articles of association of the company do not regulate all the aspects of relations between shareholders. For this reason, in jurisdictions with rich corporate law traditions it is commonly used practice to enter into a shareholders’ agreements between owners of the company.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Shareholders rights